Effect of quercetin on the rate of development and viability of bovine embryos produced in vitro - Maturana, Diana (2019)
The development rates and the quality of the bovine embryos produced in vitro are lower than those produced in vivo, due to the oxidative stress to which they are subjected during their manipulation and the culture conditions. The aim of this study was to evaluate the production, cellularity and vitality of bovine blastocysts produced in vitro with different concentrations of quercetin. A total of 2108 oocytes were matured in vitro in medium 199 with 10% FBS, 5.0 μg/ml LH and 0.5 μg/ml FSH. Fertilization was carried out in TALP medium with 2x106 spermatozoa/ml. Potential zygotes were cultured at 38.7 °C with 5% CO2 in SOF culture medium supplemented with six concentrations of quercetin (1, 5, 10, 15, 20, 50 μM) and as controls were used the SOF medium without quercetin and supplemented with DMSO. The rates of cleavage (day 2) and blastocysts (day 7) were determined, as well as the cellularity and cell viability of the blastocysts. An analysis of variance was performed, and the means of the treatments were compared with the Tukey test. Treatments with 1 and 5 μM of quercetin were higher for the blastocyst rate (p<0.05). A reduction in the cleavage rate, the blastocyst rate and cell viability were observed for 20 and 50 μM, and a decrease in cellularity for 15 μM was found. Quercetin used at low concentrations during the in vitro culture of bovine embryos produces an increase in the rate of blastocysts, while the use of high concentrations of quercetin generates deleterious effects in bovine embryos.